SYSTEMATIC REVIEW : MADU UNTUK ULKUS DIABETIKUM - Fauzi, Ahmad Kholid (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2022)
Diabetes Mellitus is a chronic disease caused by abnormalities in insulin secretion, insulin absorption or both. Characteristics of people who suffer from diabetes mellitus is an increase in blood sugar (hyperglycemia). Damage to the peripheral nervous system will reduce the response to the patient's pain or also called numbness of the peripheral tissues. Lack of sensitivity will cause the patient to be unaware of the wound. In addition to using anti-diabetic drugs and wound care, honey can also be an alternative in wound care and accelerate the healing of ulcers decubitus. Methods: This study is a literature review using research data taken from Google Scholar. The journal criteria taken are from 2017 to 2022 with the keywords honey and pressure ulcers. From the journals reviewed, it was found that honey can accelerate the healing of diabetic wounds. Healing diabetic ulcers with honey can be compared with other methods. The use of honey is cheaper than other wound healing methods. Honey as a wound dressing in diabetic wounds can improve healing at a lower cost